Does the strength of the victim-offender overlap depend on the relationship between the victim and perpetrator?. (January 2017) - Zimmerman, Gregory M.; Farrell, Chelsea; Posick, Chad
Abstract: Purpose: Strong evidence of the correlation between victimization and offending has led researchers to investigate both the causal relationship between victimization and offending and possible contingencies in this relationship. But, research has yet to investigate whether the victim's relation to the perpetrator impacts the strength of the victim-offender overlap. Drawing on betrayal trauma theory, we examine whether the victim-offender overlap depends on the relationship between the victim and the perpetrator. Methods: Using data from the Project on Human Development in Chicago Neighborhoods, a three-level logistic item response model nested 7936 violent crime item responses at level 1 within 992 subjects (at level 2) representing 174 neighborhoods across metropolitan Chicago (at level 3). Results: Victimization by a relatively unfamiliar (acquaintance) or unknown (stranger) perpetrator did not increase the likelihood of subsequent violent behavior, while victimization by a family member, peer, or gang member was significantly associated with future violence. Among known perpetrators, victimization by a family member was least likely to generate an offending response. Conclusions: Victimization and offending are inextricably linked, but the ways in which these constructs are related are nuanced. In particular, the strength of the victim-offender overlap depends on the relationship between the victim and perpetrator. Highlights: The victim-offender overlap depended on the perpetrator's relation to the victim. Known perpetrators had stronger effects on offending than did unknown perpetrators. Victimization by an acquaintance or stranger had no impact on subsequent violence. Victimization by a family member, peer or gang member increased the risk of offending.